Pemeriksaan Operasional Terhadap Aktivitas Produksi Percetakan Koran Pikiran Rakyat Untuk Meningkatkan Efektivitas dan Efisiensi Aktivitas Produksi - Felina Kusnakhin; Melissa Isabella Senastra (Universitas Kristen Maranatha, 2019)
Even sometimes called ancient and outdated, in fact, newspaper still being one of news media which is quite favourable. Even though printing activity is almost done automaticaly by machine, printing scheduling still be the challenge for production division. Operational review is a review that should be done to find out wether a company has been running effectively, efficiently, and economically. To make production activity and function run effectively, managers should be able to detect important problems and also can control and oversee the very limited resources. An optimal production isn’t only a timely production, but also a production that can minimize its waste. The research method that’s been used in this research is descriptive study method. There are two data collecting technique which is used in this research, the field research by doing interviews, observations, analysis of company data, and the library research by studying books related to this research. Meanwhile, data processing technique which is used in this research are divided into two parts, quantitative analysis and quantitative analysis to know how much loss in production division caused by waste.The result revealed that production activity in PT PR hasn’t been efective and efficient that makes impact on so many waste. There are various caused of that problems that can be grouped into three factors: plant factor, people factor, and method factor.Some recommendations to improve production’s effectiveness and efficiency by checking the machines thoroughly, provide sepcial space for putting new paper rolls, making production time target, increasing the use of imported double tape, minimizing news revision when the printing activities is almost done, and evaluate overtime activities and monitor normal work time to ensure that every worker is working optimally. Keywords: Review, Production, Waste